TGF-β induced epithelial–mesenchymal transition in an advanced cervical tumor model by 3D printing. (10th September 2018) - Pang, Y; Mao, S S; Yao, R; He, J Y; Zhou, Z Z; Feng, L; Zhang, K T; Cheng, S J; Sun, W
Abstract: An advanced in vitro cervical tumor model was established by 3D printing to study the epithelial-to-mesenchymal transition (EMT), which is a very important stage of dissemination of carcinoma leading to metastatic tumors. A HeLa/hydrogel grid construct composed of gelatin, alginate, Matrigel and HeLa cells was fabricated by forced extrusion in a layer-by-layer fashion. HeLa cells rapidly proliferated, formed spheroids and presented tumorigenic characteristic in the 3D-printed structure. With the supplement of TGF- β, aggregated HeLa cells started to disintegrate, and some of them changed into fibroblast-like spindle morphology, which indicated that EMT was induced. The down-regulation of epithelial marker E-cadherin, and up-regulation of mesenchymal markers such as snail, vimentin and N-cadherin were all observed in the 3D-printed model, and performed differently in 3D and 2D models. The TGF- β induced EMT was inhibited by the treatment of disulfiram and EMT pathway inhibitor C19 in a dose dependent manner, showing great potential for future studies of a therapeutic program towards cervical tumor metastasis.